Pengaruh Total Assets Turnover (TATO), Net Profit Margin (NPM) dan Debt to Equity Ratio Terhadap Sustainable Growth Rate pada Perusahaan Sektor Properties & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2023 - Syafira, Rania Putri; Tristanto, Triyono Adi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Sustainable Growth Rate of Indonesia Stock Exchange-listed Property & Real Estate companies from 2019 to 2023 is examined using Total Assets Turnover (TATO), Net Profit Margin (NPM), and Debt to Equity Ratio. A company's Sustainable Growth Rate indicates its potential to grow internally without outside investment. This study used multiple linear regression analysis for quantitative descriptive research. Purposive sampling comprised 17 establishments. We used annual financial reports as secondary data. Data were modified using lag to remove autocorrelation. Data analysis in SPSS Version 26 and Excel employed Descriptive Statistical Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, T Test, F Test, Correlation Coefficient Test, and Determination Coefficient Test. This study found that Total Asset Turnover (TATO) and Net Profit Margin (NPM) positively and significantly affect Sustainable Growth Rate (SGR), but not Debt-to-Equity Ratio. In this study, operational efficiency and profitability determine a company's long-term performance, not debt finance.